Soldiers' Stories Military Women in Cinema and Television since World War II - Tasker, Yvonne (Duke University Press, 2011)
From Skirts Ahoy! to M*A*S*H, Private Benjamin, G.I. Jane, and JAG, films and television shows have grappled with the notion that military women are contradictory figures, unable to be both effective soldiers and appropriately feminine. In Soldiers' Stories, Yvonne Tasker traces this perceived paradox across genres including musicals, screwball comedies, and action thrillers. She explains how, during the Second World War, women were portrayed as auxiliaries, temporary necessities of "total war." Later, nursing, with its connotations of feminine care, offered a solution to the "gender problem." From the 1940s through the 1970s, musicals, romances, and comedies exploited the humorous potential of the gender role reversal that the military woman was taken to represent. Since the 1970s, female soldiers have appeared most often in thrillers and legal and crime dramas, cast as isolated figures, sometimes victimized and sometimes heroic. Soldiers' Stories is a comprehensive ...